2013
DOI: 10.3390/polym5010077
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Cross-Linked Copolymer Membranes Based on Poly(benzoxazine) and Polybenzimidazole and Their Application to an Electrolyte Membrane for a High-Temperature PEM Fuel Cell

Abstract: Elevated-temperature (100~200 °C) polymer electrolyte membrane (PEM) fuel cells have many features, such as their high efficiency and simple system design, that make them ideal for residential micro-combined heat and power systems and as a power source for fuel cell electric vehicles. A proton-conducting solid-electrolyte membrane having high conductivity and durability at elevated temperatures is essential, and phosphoric-acid-containing polymeric material synthesized from cross-linked polybenzoxazine has dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 127 publications
1
13
0
1
Order By: Relevance
“…A PEMFC directly converts the chemical energy of hydrogen and oxygen into electricity with a proton exchange membrane (PEM) as a key component. PEMFC has been shown to exhibit effective and high energy conversion, high proton conductivities and excellent energy density [2]. The most commercialized PEM is Nafion ® , a sulfonated fluoropolymer developed by DuPont.…”
Section: Introductionmentioning
confidence: 99%
“…A PEMFC directly converts the chemical energy of hydrogen and oxygen into electricity with a proton exchange membrane (PEM) as a key component. PEMFC has been shown to exhibit effective and high energy conversion, high proton conductivities and excellent energy density [2]. The most commercialized PEM is Nafion ® , a sulfonated fluoropolymer developed by DuPont.…”
Section: Introductionmentioning
confidence: 99%
“…Although the terminal functionalization has the greatest influence on the reactivity of the oligomers (for a given molecular weight), it is noted that the phenyl rings in the oligomer backbones are also potential sites for crosslinking as Chang et al have identified in their studies of PBZs and polybenzimidazoles, albeit to a lesser degree than the conventional mechanism. Thus, from a consideration of the terminal functional groups the ostensibly nonreactive chloro‐terminated oligomer (PSU Cl ) would ultimately yield predominantly a semi‐interpenetrating network 41 ; the hydroxyl‐terminated oligomer (PSU OH ) would yield an interpenetrating network yielding both hydrogen bonded species and hydroxyl‐mediated ring opening; the full benzoxazine telechelic (PSU Bz ) would be fully coreactive in a copolymeric network.…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that the modification of membranes by copolymers with carboxylic and amino groups leads to more accurate detection of heavy metal ions. A review presented by Choi et al [39] showed the advantages of polymer membrane used at a high temperature (100~200 • C). The phosphoric-acid-containing polymeric material synthesized from cross-linked polybenzoxazine presented feasible characteristics.…”
Section: Introductionmentioning
confidence: 99%